American lake nuclear peril in the Pacific - Bello, Walden F. (Popular Book Store [distributor], 1986)
"American Lake reveals the precarious state of the American and Soviet nuclear stand-off in the Pacific. It exposes to public view for the first time the full extend of the nuclear arms race in the Pacific - a race which could trigger a global nuclear war. Using previously undisclosed and formerly classified Pentagon files, American Lake shows how World War III could start in the Pacific rather than Europe or the Middle East. Written by the authors who discovered Australia?s role in the MX missile tests, American Lake will frame the debate over the arms alliance for years to come. American Lake argues that nuclear war is not inevitable. It charts a course towards peace."--Back cover.